Хип-хоп педагогика - Нургалиев, Н.У. (My University, 2016)
The article discusses the history, methods and technology of the application of just new direction of Kazakhstani Education - hip-hop pedagogy.
Keywords: hip-hop pedagogy; rap lesson; aitys; rhythm; tonality